Edith Nesbit and Jorge Luis Borges - Bourhan el Din, Mariam (Estudios Ingleses de la Universidad Complutense, 2013)
Both Nesbit and Borges draw on esoteric notions, both invent fiction where extraordinary phenomenon play a role in understanding reality and both exploit the literary possibilities of the esoteric tradition. These affinities denote a more than coincidental correlation and suggest possible influences of the English writer on Borges’ short stories.